2023
DOI: 10.5194/bg-20-3249-2023
|View full text |Cite
|
Sign up to set email alerts
|

Past fire dynamics inferred from polycyclic aromatic hydrocarbons and monosaccharide anhydrides in a stalagmite from the archaeological site of Mayapan, Mexico

Julia Homann,
Niklas Karbach,
Stacy A. Carolin
et al.

Abstract: Abstract. Speleothems (cave stalagmites) contain inorganic and organic substances that can be used to infer past changes in local and regional paleoenvironmental conditions. Specific biomarkers can be employed to elucidate the history of past fires, caused by interactions among climate, regional hydrology, vegetation, humans, and fire activity. We conducted a simple solid–liquid extraction on pulverised carbonate samples to prepare them for analysis of 16 polycyclic aromatic hydrocarbons (PAHs) and three monos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Homann et al. (2023) found that high molecular weight PAHs were often <LOD in a Mexican speleothem. They attributed this to filtering of high molecular weight PAHs by overlying soils and epikarsts, as earlier suggested by Perrette et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Homann et al. (2023) found that high molecular weight PAHs were often <LOD in a Mexican speleothem. They attributed this to filtering of high molecular weight PAHs by overlying soils and epikarsts, as earlier suggested by Perrette et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, that low molecular weight PAHs are generally more abundant than high molecular weight PAHs, and that total PAH concentrations are higher in black and gray ashes than in white ashes both suggest that PAH-derived records of past fires may be biased toward less-severe burns. Homann et al (2023) found that high molecular weight PAHs were often <LOD in a Mexican speleothem. They attributed this to filtering of high molecular weight PAHs by overlying soils and epikarsts, as earlier suggested by Perrette et al (2013).…”
Section: Geochemistry Geophysics Geosystemsmentioning
confidence: 98%
See 3 more Smart Citations